2002
DOI: 10.1001/archderm.138.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Inflammation (Vasculitis) in Sweet Syndrome

Abstract: Background: Sweet syndrome is characterized by painful, erythematous plaques of rapid onset accompanied by fever. Absence of vasculitis is a histologic criterion for diagnosis. However, recent reports suggest that vasculitis should not exclude the diagnosis. We hypothesized that vasculitis can occur in Sweet syndrome and that it represents an epiphenomenon rather than a primary immune-mediated process.Design: Skin biopsy specimens from patients with Sweet syndrome were reviewed to determine the prevalence of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(32 citation statements)
references
References 14 publications
2
26
0
1
Order By: Relevance
“…This agrees with 2 histologic series that identified leukocytoclastic vasculitis or vasculitislike changes in 18% to 30% of cases of typical Sweet syndrome. 23, 24 Malone et al 23 reviewed the presence of vasculitis in Sweet syndrome in relation to the timing of the biopsy and found that vasculitis correlated with lesions of longer duration. Indeed, 1 of our patients (case 8) had an initial biopsy result negative for vasculitis, then a subsequent positive biopsy result, suggesting a difference in lesion timing or sampling rather than a fundamental change in the disease process.…”
Section: Commentmentioning
confidence: 99%
“…This agrees with 2 histologic series that identified leukocytoclastic vasculitis or vasculitislike changes in 18% to 30% of cases of typical Sweet syndrome. 23, 24 Malone et al 23 reviewed the presence of vasculitis in Sweet syndrome in relation to the timing of the biopsy and found that vasculitis correlated with lesions of longer duration. Indeed, 1 of our patients (case 8) had an initial biopsy result negative for vasculitis, then a subsequent positive biopsy result, suggesting a difference in lesion timing or sampling rather than a fundamental change in the disease process.…”
Section: Commentmentioning
confidence: 99%
“…Twelve cases satisfied the diagnostic criteria for SS. 18 Sixteen patients presented with BD, diagnosed according to the criteria proposed by the International Study Group for Behçet's Disease. 19,20 All patients were further divided according to either active or inactive state of the disease.…”
Section: Clinical Investigationmentioning
confidence: 99%
“…Histological examination revealed lymphocytic infiltration. Although this histological finding differs from Sweet's syndrome, vasculitis may be secondary to immunemediated processes in this disease [45]. This is also true for evaluation of the patients with cardiovascular diseases with aortitis, where histologic findings showed both lymphocytic and polymorphonuclear infiltration [11,28].…”
Section: Discussionmentioning
confidence: 68%